Decline in radioiodine use but not total thyroidectomy in thyroid cancer patients treated in the United Arab Emirates - A retrospective study. (April 2021) - Azhar, Malik; Aziz, Faisal; Almuhairi, Salama; Alfelasi, Mohammad; Elhouni, Ali; Syed, Rizwan; Al-Shamsi, Humaid O.; Aldahmani, Khaled M.
Abstract: Objectives: To assess the trend of clinicopathological features and treatment modalities in patients with thyroid cancer (TC) in the largest oncology center in the United Arab Emirates (UAE). Methods: A retrospective analysis of patients with TC presenting to a tertiary care hospital in Al Ain, UAE between September 2008 and December 2018 identified using ICD 9 & 10 codes was performed. Data on demographics, histopathology, surgical extent, and use of Radioiodine (RAI) were extracted. Exact logistic and ordinal logistic regressions were performed to analyze the annual trend in features and management of TC, and logistic regression analysis was performed to identify predictors of total thyroidectomy and RAI use. Results: A total of 762 patients were included in the analysis (mean age: 39.6 ± 12.6 years, 45 (60%) women). The majority (92.2%) were diagnosed with papillary thyroid cancer (PTC) and 83.9% had tumor size of <4 cm. All patients underwent surgery (93.8% total thyroidectomy, 6.2% lobectomy) and 77.4% received RAI therapy overall with a significant (p < 0.001) decline from 100% in 2008 to 60% in 2018. In multivariate analysis, nationality, and lymph node (LN) involvement were significant predictors of total thyroidectomy, while nationality, LNs, year of diagnosis, and tumor size significantly predicted RAI use. Conclusion: Most patients in our cohort were diagnosed with localized PTC with no significant change in the extent of surgical approach but a substantial decline in RAI therapy administration over time. Nationality and LN involvement were significant predictors of surgical extent and RAI use. Highlights: This is the largest study evaluating clinicopathological features and treatment modalities in TC patients in the UAE. Most patients were diagnosed with localized PTC. A substantial decline in RAI therapy administration but not the extent of thyroidectomy was observed during the study period. Nationality and LN involvement were significant predictors of surgical extent and RAI use.